The complete mitochondrial genome and phylogenetic analysis of a leaf insect Cryptophyllium oyae Cumming & Le Tirant, 2020 (Phasmatodea: Phylliidae) in China - Guichun Liu; Zecheng Du; Baozhen Zhou; Zhiwei Dong; Lei Chen; Jianyue Qiu (Mitochondrial DNA. Part B. Resources)
Stick insects have evolved remarkable camouflage adaptations, but their geographical distribution and phylogeny remain insufficiently understood. In this study, we confirmed the presence of Cryptophyllium oyae Cumming and Le Tirant in China, and presented its complete mitochondrial genome (16,820 bp) for the first time. The genome consists of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a control region. Additionally, a phylogenetic tree using mitochondrial genomes from 51 Phasmatodea species confirmed C. oyae belongs to the Phylliidae clade. This study enhances taxonomic identification and provides insights for phylogenetic analysis and conservation of Phasmatodea species in future studies.